2007
DOI: 10.1074/jbc.m703424200
|View full text |Cite
|
Sign up to set email alerts
|

A Global Transcriptional Regulator in Thermococcus kodakaraensis Controls the Expression Levels of Both Glycolytic and Gluconeogenic Enzyme-encoding Genes

Abstract: We identified a novel regulator, Thermococcales glycolytic regulator (Tgr), functioning as both an activator and a repressor of transcription in the hyperthermophilic archaeon Thermococcus kodakaraensis KOD1. Tgr (TK1769) displays similarity (28% identical) to Pyrococcus furiosus TrmB (PF1743), a transcriptional repressor regulating the trehalose/maltose ATP-binding cassette transporter genes, but is more closely related (67%) to a TrmB paralog in P. furiosus (PF0124). Growth of a tgr disruption strain (⌬tgr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 54 publications
4
108
0
Order By: Relevance
“…furiosus, and Tco. kodakarensis (31,178,207,208). Furthermore, in most cases, PGK and GAPDH show a pronounced preference for the anabolic direction, as deduced from their kinetic properties (176,178,185,198,200).…”
Section: Glyceraldehyde-3-phosphate Dehydrogenase/phosphoglycerate Kimentioning
confidence: 99%
“…furiosus, and Tco. kodakarensis (31,178,207,208). Furthermore, in most cases, PGK and GAPDH show a pronounced preference for the anabolic direction, as deduced from their kinetic properties (176,178,185,198,200).…”
Section: Glyceraldehyde-3-phosphate Dehydrogenase/phosphoglycerate Kimentioning
confidence: 99%
“…One interesting example involved the in vivo disruption and analysis of a gene encoding reverse gyrase on the T. kodakaraensis genome, which revealed that the gene product functions in adaptation to high temperature, because reverse gyrase is highly conserved only in hyperthermophiles (Atomi et al, 2004). These efficient genetic tools have already been used to investigate several biological systems, such as the glycolysis pathway (Yoshida et al, 2006;Matsumi et al, 2007), natural product biosynthesis (Yokooji et al, 2009;Borges et al, 2010), transcription factors (Kanai et al, 2007(Kanai et al, , 2010, and operon transcription and translation machinery Hirata et al, 2008). However, these useful and powerful techniques have not yet been applied to the analysis of DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…The ortholog of TrmBL1 in Thermococcus kodakarensis, named Tgr (Thermococcales glycolytic regulator), was found to prominently recognize the palindromic TGM (Thermococcales glycolytic motif) sequence [6,7]. Depending on its position within the respective promoter, Tgr binds to it, acting as an activator when present upstream of BRE/TATA box of genes encoding gluconeogenic proteins but as a repressor when positioned downstream of the BRE/ TATA box of genes encoding glycolytic genes.…”
Section: Introductionmentioning
confidence: 99%